Pengaruh Strategi Bisnis dan Good Corporate Governance Terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2020 – 2022 - Dwi Laksita Nalurita; Desmiyawati; Rheny Afriana Hanif (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to examine the influence of business strategy, institutional ownership, managerial ownership, independent commissioners, and audit committees on company value. The population in this study are manufacturing sector companies listed on the Indonesian Stock Exchange for the 2020 – 2022 period. The sample selection technique uses a purposive sampling method. The sample selected in this research was 84 companies based on predetermined criteria. This research uses secondary data obtained from annual reports and financial reports. The analytical method used is multiple linear regression analysis using SPSS version 26. The research results show that the business strategy variable influences company value with a significance value of 0.033 < 0.05. The institutional ownership influences company value with a significance value of 0.031 < 0.05. Managerial ownership influences company value with a significance value of 0.015 < 0.05. Independent commissioners influence company value with a significance value of 0.000 < 0.05. The audit committee has no effect on company value with a significance value of 0.358 > 0.05.